Early Discharge from the Emergency Department Based on Soluble Urokinase Plasminogen Activator Receptor (suPAR) Levels: A TRIAGE III Substudy. (19th May 2019) - Schultz, Martin; Rasmussen, Line J. H.; Høi-Hansen, Thomas; Kjøller, Erik; Jensen, Birgitte N.; Lind, Morten N.; Ravn, Lisbet; Kallemose, Thomas; Lange, Theis; Køber, Lars; Rasmussen, Lars S.; Eugen-Olsen, Jesper; et al.
Abstract : Objective . Using biomarkers for early and accurate identification of patients at low risk of serious illness may improve the flow in the emergency department (ED) by classifying these patients as nonurgent or even suitable for discharge. A potential biomarker for this purpose is soluble urokinase plasminogen activator receptor (suPAR). We hypothesized that availability of suPAR might lead to a higher proportion of early discharges. Design . A substudy of the interventional TRIAGE III trial, comparing patients with a valid suPAR measurement at admission to those without. The primary endpoint was the proportion of patients discharged alive from the ED within 24 hours. Secondary outcomes were length of hospital stay, readmissions, and mortality within 30 days. Setting . EDs at two university hospitals in the Capital Region of Denmark. Participants . 16, 801 acutely admitted patients were included. Measurements and Main Results . The suPAR level was available in 7, 905 patients (suPAR group), but not in 8, 896 (control group). The proportion of patients who were discharged within 24 hours of admittance was significantly higher in the suPAR group compared to the control group (50.2% (3, 966 patients) vs. 48.6% (4, 317 patients), P = 0.04 ). Furthermore, the mean length of hospital stay in the suPAR group was significantly shorter compared to that in the control group (4.3 days (SD 7.4) vs. 4.6 days (SD 9.4), P = 0.04 ). In contrast, the readmission rate within 30 days was significantly higher in the suPAR group (10.6% (839 patients) vs. 8.8% (785 patients), P < 0.001 ). Among patients discharged within 24 hours, there was no significant difference in the readmission rate or mortality within 30 days. Readmission occurred in 8.5% (336 patients) vs. 7.7% (331 patients) (P = 0.18 ) and mortality in 1.3% (52 patients) vs. 1.8% (77 patients) (P = 0.08 ) for the suPAR group and control group, respectively. Conclusion . These post hoc analyses demonstrate that the availability of the prognostic biomarker suPAR was associated with a higher proportion of discharge within 24 hours and reduced length of stay, but more readmissions. In patients discharged within 24 hours, there was no difference in readmission or mortality. Trial Registration of the Main Trial . This trial is registered withNCT02643459 .